A gold nanoparticle-intercalated mesoporous silica-based nanozyme for the selective colorimetric detection of dopamine. Issue 2 (8th January 2020) - Ray, Shounak; Biswas, Rima; Banerjee, Rumeli; Biswas, Papu
Abstract : A AuNP nanoparticle-incorporated mesoporous silica-based nanozyme exhibited the peroxidase-like activity and was utilized for the selective colorimetric detection of dopamine. Abstract : Highly dispersed aggregation-free gold nanoparticles intercalated into the walls of mesoporous silica (AuMS) were synthesized using thioether-functionalized silica as a nanozyme, which exhibited an excellent peroxidase mimic activity. The AuMS material was characterized via XRD, N2 adsorption–desorption, FESEM, SEM-EDS particle mapping, TEM, and XPS. The peroxidase-like activity of the AuMS material was studied thoroughly, and the effect of pH and temperature was evaluated. The reproducibility of the peroxidase mimic activity and long-term stability of the AuMS catalyst were also studied. Furthermore, the AuMS catalyst was successfully utilized for the detection and quantification of dopamine, an important neurotransmitter, colorimetrically with a linear range of 10–80 μM and a limit of detection (LOD) value of 1.28 nM. The determination of dopamine concentration in commercially available dopamine hydrochloride injection showed high accuracy, good reproducibility, and high selectivity in the presence of uric acid, ascorbic acid, glucose, tryptophan, phenylalanine, and tyrosine.